2020
DOI: 10.9744/jmk.22.2.99-114
|View full text |Cite
|
Sign up to set email alerts
|

THE IMPACT OF ENTREPRENEURIAL ORIENTATION ON SMEs PERFORMANCE IN GHANA: THE ROLE OF SOCIAL CAPITAL AND GOVERNMENT SUPPORT POLICIES

Abstract: The primary purpose of this study was to propose a conceptual framework on the impact of entrepreneurial orientation (EO) on SMEs performance in Ghana: The role of social capital (SC) and government support policies (GSPs). The study re­viewed existing literature pertaining the five dimensions of EO and used measures of SC, and GSPs in relation to SMEs performance in Ghana. This study would be anchored on two theories thus the resource-based view and the social capital theories stressing the need for SMEs to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 233 publications
1
11
0
1
Order By: Relevance
“…This success inspires Malaysian SME owners because key components also need to be considered, such as non-financial performance. It doesn't stop there, Yatim et al (2019) and Zaato et al (2020) verified the conceptual framework for reviewing the enthusiasm of SMEs. In fact, government support has reconstructed social capital and entrepreneurial orientation.…”
mentioning
confidence: 99%
“…This success inspires Malaysian SME owners because key components also need to be considered, such as non-financial performance. It doesn't stop there, Yatim et al (2019) and Zaato et al (2020) verified the conceptual framework for reviewing the enthusiasm of SMEs. In fact, government support has reconstructed social capital and entrepreneurial orientation.…”
mentioning
confidence: 99%
“…So that without face-to-face learning, the Tuweb learning system can be implemented properly and obtain the same student learning achievements. Other research with blended learning objects with a combination of face-to-face learning and online learning at UT obtained the same results, namely students get satisfaction but ignore technological factors (Zaato et al, 2023). This is because the blended learning objects used still consist of face-to-face learning elements and the respondents also come from students who received scholarships so that in terms of financial ability they are still lacking.…”
Section: Discussionmentioning
confidence: 71%
“…Al Hakimi, et.all (2021) [17] defined market orientation as the most effective and efficient organizational culture to create behaviors that can produce the best for buyers and produce superior performance for the company. Based on the two definitions of market orientation, it can be concluded that market orientation is a way for organizations to identify markets and use them as a basis for determining company strategy [18], [12]. Companies that are successful in controlling the market are referred to as market drive firms, namely companies that always place customer orientation and competitor orientation in harmony, resulting in better marketing performance.…”
Section: Market Orientationmentioning
confidence: 99%